Effects of woodland restoration and management on the community of surface-active arthropods in the metropolitan Chicago region. (October 2015) - McCary, Matthew A.; Martínez, José-Cristian; Umek, Lauren; Heneghan, Liam; Wise, David H.
Highlights: We examined how comprehensive vegetation management alters woodland arthropods. Activity-densities of non-native isopods were highest in unmanaged woodlands. Springtails (entomobryid Collembola) and wolf spiders were highest in managed sites. The shift in arthropod community structure was correlated with invasive-plant cover. We conclude that woodland vegetation management also restores arthropod communities. Abstract: Restoration of woodlands that have been invaded by exotic plants has primarily focused on restoring vegetation structure by removing invaders and planting native species that have declined in abundance. Management practices to date continue to focus on plant communities, but if restoring ecosystem integrity is the goal of restoration, knowledge of how the fauna has recovered is essential. We examined the impact of vegetation restoration and management on the surface-active arthropod community across a spectrum of 22 woodland sites in the greater metropolitan Chicago region. Sites were grouped into three categories based on existing condition. Invaded sites had never been restored or managed (" Control ", n  = 5); had been undergoing restoration for 3–21 years (" Managed-int ", n  = 12) but were not yet near the management goal; or were restored plots (11–21 years of management) that land managers identified as representative of their restoration target based upon the vegetation present (" Managed-REF ", n  = 5). Each site was a one-ha plot containing four pitfall traps used to assess activity-densities of 35 taxa of epigeic arthropods. Permutational analysis of variance (PERMANOVA) and subsequent canonical analysis of principal coordinates (CAP) revealed that arthropod community structure varied between Control and Managed-REF sites, with the Managed-int sites demonstrating convergence toward the Managed-REF . The activity-densities of non-native isopods (detritivores) were nearly twice as high in Control sites compared to Managed-REF sites, whereas traps in Managed-REF sites had four times the number of Collembola (fungivores). Distance-based redundancy analysis (dbRDA) revealed that invasive woody plant cover and rates of uptake of soil P and NO3 − by root simulators explained over 40% of the variation in arthropod community structure. Our findings suggest that restoration management targeted at the vegetation also restores the arthropod community in woodlands to a composition that has fewer non-native arthropods.